Assessment of the genotoxic potential of temephos - Cobanoglu, Hayal; Cayir, Akin (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2021)
Genotoxic effects of pesticides are of great concern for public health due to the fact that they are widely used for both domestic and industrial purposes. Temephos is a member of organophosphorus pesticides, which is the most widely used group of chemicals against both agricultural and domestic insects. We therefore aimed in the present study to investigate the genotoxic and cytotoxic effects of temephos on human peripheral blood lymphocytes, using the cytokinesis-block micronucleus (CBMN) and sister chromatid exchange assays. The results showed that micronucleus (MN) frequency increased at concentrations of 50 and 75 μg/ml аlthough it was not found statically significant (p>0.05). We found that sister chromatid exchange (SCE) values at concentrations of 50 and 75 μg/ml were significantly higher than those obtained for the control (p0.05). It can be concluded that temephos was not cytotoxic at concentrations of 25, 50 and 75 μg/ml. However, it may have a genotoxic potential in human peripheral lymphocytes.
Keywords: Pesticide exposure, genetic damage, micronucleus, sister chromatid exchange, cytostatic effect